From Internal to External: Integrating Corporate Communications in the Digital Age - Edwin Juniarta; Saprida Saprida; Fadilla Fadilla; Havis Aravik; Ahmad Tohir (Penerbit dan Percetakan CV.Picmotiv, 2026)
With the development of digital technology, corporate communication patterns have shifted from separate internal and external communications to more integrated communications. This is necessary to improve relationships with various stakeholders and create information alignment. The purpose of this study is to examine how integrated corporate communications are implemented in the digital era and identify opportunities and barriers to its implementation. This study employed a qualitative approach and utilized library research to examine various relevant sources. According to the research findings, integrated communications can improve organizational coordination, maintain message consistency, strengthen corporate image, and build better relationships with the public and customers. However, companies must face challenges due to rapid technological advances and demands for transparency. Therefore, to maintain corporate competitiveness and sustainability in the digital era, an integrated communications strategy is crucial.